Biological Activities of the Methanolic Extracts of Coccinia indica and Mikania scandens Leaves Available in Bangladesh - Ekram, Md Akhtar E; Sarker, Md Enamul Haq; Talukder, Afrin Priya; Sarker, Badhan; Uddin, Md Salah; Zaman, Shahriar (Dhaka University Journal of Pharmaceutical Sciences, 2017)
Biological activities of the methanolic leaf extracts of Coccinia indica and Mikania scandens were observed through antimicrobial assay, cytotoxic assay and antioxidant activity through DPPH (1,1-diphenyl-2- picrylhydrazyl) radical scavenging assay with a comparison of IC50 values of extracts with standard antioxidant BHT (butylatedhydroxytoluene). In case of crude extract of Coccinia indica, antimicrobial assay showed that Pseudomonas sp., Escherichia coli were susceptible at a dose of 150?g/disc out of five tested bacteria. Again, out of five fungi strains, Phytopthora sp., Penicillium notatum, Aspergillus niger were sensitive against 150 ?g/disc containing crude extract. In the case of Mikania scandens, antimicrobial assay showed that Pseudomonas sp., Rhizobium for Vigna mongu (RVM), Rhizobium for Cicer arietinum (RCA)were susceptible at a dose of 150 ?g/disc, while Escherichia coli was susceptible at only 75 ?g/disc. Furthermore, out of five fungi strains, Phytopthora sp., Penicillium notatum were sensitive against 150?g/disc while Aspergillus niger was sensitive against 100 ?g/disc and 150 ?g/disc of M. scandens crude extract. The DPPH free radical scavenging activity of C. indica leaf extract displayed that it was capable of scavenging the 50% DPPH at the dose of 130 ?g/ml and itindicated that the plant extract had moderate to high antioxidant activity. However, Mikania scandens, the IC50 value was 125?g/ml which indicated that M. scandens leaf extract had strong antioxidant potentialities than the leaf extract of C. indica. Cytotoxic assay showed that the methanolic leaf extracts of C. indica and M. scandens were highly toxic for the aquatic organisms at the concentrations of above 104.60 and 89 ?g/ml, respectively. Dhaka Univ. J. Pharm. Sci. 16(1): 87-93, 2017 (June)